Implementation of Transport Protocols Using Parallelism and VLSI Components DOI: 10.14209/jcis.1994.4 - Braun, Torsten; H. Schiller, Jochen; Zitterbart, Martina (Journal of Communication and Information Systems, 2015)
Service requirements and performance needs are increasingly demanding in emerging high performance communication subsystems. Well-suited protocols and efficient protocol implementation techniques form the core of such systems. Applying parallelism and introducing VLSI components to overcome system bottlenecks represent promising approaches towards highly efficient implementations. This paper discusses experiments with parallel protocol implementations and introduces a protocol especially designed to support parallelism. Moreover. a parallel VLSI architecture is introduced enabling fine-grained parallelism among protocol functions as well as coarse grain parallelism among connections. Dedicated VLSI components are used for potential bottleneck functions, such as timer and memory management or retranmission support.